Application and method of deep arsenic removal in sewage by ternary cationic framework MOF material MAF-stu-2

By using the ternary cationic frame MOF material MAF-stu-2, the ion exchange mechanism is used to adsorb As(V) in water, the problems of poor arsenic removal effect and slow adsorption rate in the prior art are solved, and the rapid depth of arsenic in water are achieved Removal, meets drinking water standards, and has good anti-interference and renewability.

CN118993246BActive Publication Date: 2025-02-11SHANTOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411467470.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-11
Estimated Expiration
2044-10-21

Smart Images

  • Figure CN118993246B_ABST
    Figure CN118993246B_ABST
Patent Text Reader

Abstract

The present invention relates to an application and method of a ternary cationic framework MOF material MAF-stu-2 for deep arsenic removal in sewage. The general structural formula of MAF-stu-2 is [Zn 3 (C 18 H 18 N 6 ) 3 (NO 3 )](NO 3 ) 5 . The method for deep arsenic removal in sewage by MAF‑stu‑2 comprises: immersing the ternary cationic framework MOF material MAF‑stu‑2 in arsenic-containing sewage and letting it stand for 1‑10 days. The present invention uses the ternary cationic framework MOF material MAF‑stu‑2 as an arsenic ion adsorbent to achieve rapid and deep arsenic removal in trace As(V) anion ion aqueous solution; pentavalent arsenic anion ion pollutants in water can be quickly and deeply removed through ion exchange; the concentration of As(V) in the solution is reduced to the drinking water threshold (<10ppb) specified by the World Health Organization (WHO), meeting the World Health Organization drinking water standards; the cationic framework MOF adsorbent exhibits rapid adsorption kinetics, high selectivity, resistance to interference from foreign ions and good cyclic stability for As(V) anion pollutants, and has broad market value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is applied to the field of wastewater treatment, and specifically relates to the application and method of ternary cation framework MOF material MAF-stu-2 in deep arsenic removal in sewage. Background Art

[0002] Freshwater resources are one of the most utilized resources by humans. With the advent of the Industrial Revolution, people have had an unprecedented impact on them. According to statistics, the world produces about 4 billion tons of industrial and domestic waste every year. Most industries, such as textiles, leather manufacturing, food processing, papermaking, brewing, etc., discharge untreated pollutants into freshwater resources, which is the biggest factor causing the pollution and shortage of global freshwater resources. This has caused the total number of people facing water shortages in the world to surge from 240 million to 3.8 billion in the past decade, while the use of freshwater has increased fourfold. The increasing demand for freshwater resources has led to the rapid development of wastewater treatment, that is, the recycling and treatment of wastewater for reuse. One of the most important aspects of developing technologies for recycling and treating wastewater is how to effectively remove new pollutants in the water.

[0003] Arsenic is classified as a Class A carcinogen by the World Health Organization (WHO). It is a highly toxic and widespread water pollutant. The WHO stipulates that the safe content of arsenic in drinking water must be less than 10 ppb. Generally, in water, arsenic is easily converted into As(V) under oxidative conditions and exists in the form of anion ions. In water bodies with a pH of 7, As(V) is mainly present in the form of HAsO4 2- exists in the form of.

[0004] At present, many materials for removing arsenic from aqueous solutions have been reported, such as activated carbon, metal oxides, etc. However, these traditional adsorption materials cannot achieve deep and efficient removal of arsenic from aqueous solutions due to low adsorption capacity, poor separation selectivity, slow adsorption rate, etc. Therefore, it is urgent to develop new arsenic adsorption materials with high efficiency and stable properties. Summary of the invention

[0005] The present invention aims to solve the problems of poor removal effect, inability to deeply remove arsenic and slow adsorption rate of existing arsenic removal materials in wastewater, and provides an application and method of ternary cationic framework MOF material MAF-stu-2 for deep arsenic removal in sewage. The ternary cationic framework MOF material MAF-stu-2 of the present invention can quickly adsorb As(V) in water to achieve deep arsenic removal.

[0006] Application of ternary cation framework MOF material MAF-stu-2 in deep arsenic removal in sewage, wherein the general structural formula of the ternary cation framework MOF material MAF-stu-2 is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5.

[0007] The MOF adsorption material for efficient arsenic removal in the present invention is synthesized by a solvothermal method from an organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene TMeImB and zinc nitrate hexahydrate. It is a ternary cationic framework MOF material for removing arsenic anions from water based on an ion exchange mechanism, wherein the ternary components include Zn 2+ , organic ligand TMeImB and bridge-coordinated NO3 - The general structural formula is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, named MAF-stu-2, NO3 - As counter anions, they are distributed on the pore surface and can exchange ions with arsenic anions in water. The crystal structure belongs to P -3 space group, a = b =22.2141(2) Å, c =11.3776(1)Å, α = β =90°, γ =120°, the network structure is sln.

[0008] Furthermore, the preparation method of the ternary cationic framework MOF material MAF-stu-2 is: dissolve zinc nitrate hexahydrate and the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene in methanol with a volume ratio of 3:1 respectively, and then add the methanol solution of zinc nitrate hexahydrate drop by drop into the methanol solution of the organic ligand and stir rapidly at room temperature, let it stand after the addition is completed, filter, wash and dry; wherein the mass ratio of zinc nitrate hexahydrate and the organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene is 1:1-1.2.

[0009] The method for deep arsenic removal in sewage using ternary cation framework MOF material MAF-stu-2 comprises soaking the ternary cation framework MOF material MAF-stu-2 in sewage containing arsenic and letting it stand for 1-10 days. After use, the adsorbate is filtered out; the general structural formula of the ternary cation framework MOF material MAF-stu-2 is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5.

[0010] Furthermore, when the arsenic concentration in the sewage is greater than 200 ppm, the addition amount of the ternary cation framework MOF material MAF-stu-2 is 1-2 mg / mL, and the standing time is 1-10 days.

[0011] Furthermore, when the arsenic concentration in the sewage is less than 10 ppm, the addition amount of the ternary cation framework MOF material MAF-stu-2 is 0.3-0.6 mg / mL, and the standing time is 1-2 days.

[0012] Furthermore, when the arsenic concentration in the sewage is 10-200 ppm, the addition amount of the ternary cation framework MOF material MAF-stu-2 is 0.6-1 mg / mL, and the standing time is 1-5 days.

[0013] The general structure of the product obtained by arsenic removal from wastewater with high arsenic concentration by ternary cationic framework MOF material MAF-stu-2 is [Zn3(C 18 H 18 N6)2(AsO4)2], belongs to P 21 / n space group, a =16.31092(9), b =19.98092(11), c =24.46205(18) Å, α = γ =90°, β =107.3951(7)°.

[0014] The material MAF-stu-2 of the present invention can reach adsorption equilibrium after 24 hours in a Na2HAsO4 solution with an initial concentration of 200 ppm, and the adsorption amount is 68.25 mg / g, which can achieve rapid arsenic removal from water; the MAF-stu-2 material is immersed in a Na2HAsO4 solution with a concentration of 200 ppm for one week, and can be phase-transformed into a ternary neutral framework MOF material, wherein the ternary components include Zn 2+ , organic ligand TMeImB and bridged coordinated AsO4 2- The general structural formula is [Zn3(C 18 H 18 N6)2(AsO4)2], belongs to P 21 / n space group, a =16.31092(9), b =19.98092(11), c =24.46205(18) Å, α = γ =90°, β=107.3951(7)°, and a new network structure was obtained, named MAF-stu-2-AsO4; in a Na2HAsO4 solution with an initial concentration of 10 ppm, MAF-stu-2 can reduce the concentration of As(V) in water to 5 ppb, reaching the drinking water standard stipulated by the World Health Organization (WHO), that is, the concentration of As(V) is less than 10 ppb, and has good anti-interference and regeneration capabilities.

[0015] The novel ternary hybrid cationic framework material MAF-stu-2 of the present invention exhibits excellent arsenic ion removal ability in aqueous solution.

[0016] (1) MAF-stu-2 crystalline material at 500 ppm HAsO4 2- In aqueous solution, an ultra-high arsenic adsorption capacity of 94 mg / g can be achieved.

[0017] (2) MAF-stu-2 crystalline material at 200 ppm HAsO4 2- In aqueous solution, adsorption equilibrium can be reached within one day, with ultrafast arsenic adsorption kinetics, and the corresponding adsorption amount is 68.25 mg / g.

[0018] (3) MAF-stu-2 crystalline material can purify the world's most severely arsenic-contaminated water source (5 ppm) to meet the World Health Organization (WHO) drinking water standards (concentration below 10 ppb). The material can reduce the As(V) concentration of 10 ppm to 2 ppm within 2 minutes, with a removal rate of up to 89.1% within 40 minutes. After 24 hours, the As(V) concentration is reduced to 5 ppb, with an arsenic removal rate of up to 99.9%.

[0019] When the arsenic ion concentration is low, the ternary cation framework MOF material MAF-stu-2 mainly relies on anion exchange for adsorption. When the arsenic ion concentration is high, MAF-stu-2 will undergo structural reconstruction.

[0020] Compared with the currently available materials, the present invention uses the ternary cationic framework MOF material MAF-stu-2 as an arsenic ion adsorbent in an aqueous solution of trace As(V) anion ions; pentavalent arsenic anion ion pollutants in water can be quickly and deeply removed through ion exchange, and arsenic can be deeply removed, reducing the concentration of As(V) in the solution to the drinking water threshold specified by the World Health Organization (WHO) (<10 ppb), meeting the World Health Organization's drinking water standards; and it exhibits rapid adsorption kinetics, high selectivity, resistance to interference from foreign ions and good cyclic stability for As(V) anion pollutants, and has broad market value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the structure of the MAF-stu-2-AsO4 material of Example 3.

[0022] Figure 2 This is a structural comparison diagram of MAF-stu-2 and MAF-stu-2-AsO4 materials.

[0023] Figure 3 This is the adsorption isotherm of As(V) anion ions by MAF-stu-2 in Example 4 at room temperature.

[0024] Figure 4 The powder X-ray diffraction patterns of MAF-stu-2 in Example 4 after being immersed in As(V) anion solutions with different concentrations for 3 days.

[0025] Figure 5 This is the Langmuir linear fitting model of the As(V) adsorption isotherm of MAF-stu-2 in Example 4.

[0026] Figure 6 This is the Freundlich linear fitting model of the As(V) adsorption isotherm of MAF-stu-2 in Example 4.

[0027] Figure 7 This is the kinetic adsorption curve of MAF-stu-2 in Example 5 in a 200 ppm As(V) anion solution.

[0028] Figure 8 The powder X-ray diffraction patterns of MAF-stu-2 in Example 5 after being immersed in a 200 ppm As(V) anion ion solution for different time periods.

[0029] Fig. 9 This is the pseudo-first-order kinetic linear fitting model of the kinetic adsorption curve of As(V) adsorption by MAF-stu-2 in Example 5.

[0030] Fig.10 This is the pseudo-second-order kinetic linear fitting model of the kinetic adsorption curve of As(V) adsorption by MAF-stu-2 in Example 5.

[0031] Fig.11 This is the kinetic adsorption curve of MAF-stu-2 in Example 6 in a 10 ppm As(V) anion solution.

[0032] Fig.12 This is the pseudo-first-order kinetic linear fitting model of the kinetic adsorption curve of As(V) adsorption by MAF-stu-2 in Example 6.

[0033] Fig.13This is the pseudo-second-order kinetic linear fitting model of the kinetic adsorption curve of As(V) adsorption by MAF-stu-2 in Example 6.

[0034] Fig.14 This is a bar chart comparing the performance of MAF-stu-2 in Example 6 for adsorbing As(V) under different concentrations and interferences of different common anions.

[0035] Fig.15 This is a bar chart showing the performance of MAF-stu-2 in Example 6 for cyclic adsorption of As(V). DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0037] Example 1

[0038] Preparation of large-size single crystal materials of MAF-stu-2

[0039] 5 mg of organic ligand TMeImB and 5 mg of zinc nitrate hexahydrate were dissolved in a mixed solvent containing 3 mL of methanol and 1 mL of deionized water, and then transferred to a sealed glass tube and reacted at 120 °C for 72 hours. After the reaction, it was slowly cooled to room temperature in the air. After repeated rinsing with methanol and deionized water, a relatively pure ternary hybrid cationic framework MOF material was obtained after filtration and drying. The material was named MAF-stu-2. The general structural formula is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, named MAF-stu-2, NO3 - As counter ions, it is distributed on the pore surface and can exchange ions with arsenic anions in water. The crystal structure belongs to P -3 space group, a = b =22.2141(2) Å, c =11.3776(1)Å, α = β =90°, γ =120°, the network structure is sln.

[0040] Example 2

[0041] Synthesis of MAF-stu-2 Powder Crystalline Material

[0042] Dissolve 1.2 g TMeImB in 300 mL methanol, and 1.2 g Zn(NO3)2·6H2O in 100 mL methanol. Add the methanol solution of Zn(NO3)2·6H2O drop by drop into the methanol solution of TMeImB under magnetic stirring. Stop stirring after the addition is complete, and let stand at room temperature for 6-12 hours to obtain a non-precipitating white emulsion. Filter by centrifugation, wash repeatedly with methanol and deionized water three times, and vacuum dry at 100 °C for one day to obtain a large amount of MAF-stu-2 powder material. The general structural formula is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, named MAF-stu-2, NO3 - As counter ions, it is distributed on the pore surface and can exchange ions with arsenic anions in water. The crystal structure belongs to P -3 space group, a = b =22.2141(2) Å, c =11.3776(1)Å, α = β =90°, γ =120°, the network structure is sln.

[0043] Example 3

[0044] Synthesis of Large-Size Single Crystals of MAF-stu-2-AsO4

[0045] Take 5-20 mg of MAF-stu-2 large-size single crystals and soak them in 20 mL of 200 ppm As(V) solution. After standing for one week, the colorless needle-shaped MAF-stu-2 crystals recrystallize into colorless cubic crystals, named MAF-stu-2-AsO4. The structure is tested by single crystal X-ray diffraction. The crystal structure is shown in Figure 1 The general structural formula is [Zn3(C 18 H 18 N6)2(AsO4)2], the space group is P 21 / n, the unit cell parameters are a =16.31092(9), b =19.98092(11), c =24.46205(18) Å, α = γ =90°, β =107.3951(7)°.

[0046] The comparison results of the crystal structures of MAF-stu-2 and MAF-stu-2-AsO4 are shown in Figure 2As shown, MAF-stu-2 is composed of a tetracoordinated mononuclear Zn 2+ With ligand TMeImB and NO3 - The self-assembled cationic framework, while MAF-stu-2-AsO4 is AsO4 3- Replace NO3 - , two AsO4 3- With three Zn 2+ The hexacoordinated trinuclear metal cluster [Zn3As2O8] is formed, and finally reconstructed into a neutral framework structure with TMeImB. MAF-stu-2-AsO4 crystals have very high stability.

[0047] Example 4

[0048] Study on the performance of MAF-stu-2 in removing arsenic anion ions from water

[0049] (1) Take 10 mg of MAF-stu-2 powder material and place it in 10-500 ppm HAsO4 2- The aqueous solution was kept at 25 °C and 120 rpm in a shaker for 24 hours. The mixed solution was then separated by centrifuge and the remaining HAsO4 was detected by atomic emission spectroscopy (ICP) of the supernatant. 2- Concentration, the results are as follows Figure 3 As shown, it can be seen from the isothermal adsorption line that when the initial concentration is 500 ppm, the material reaches adsorption saturation for arsenic anions in aqueous solution, and the adsorption capacity is as high as 94 mg / g.

[0050] (2) After the material was placed in the solution described in (1) and adsorbed for 72 hours, the mixed solution was centrifuged and the PXRD test was used to test the changes in the sample structure before and after adsorption. The results are as follows Figure 4 As shown, it can be seen that there are no impurity peaks in the diffraction pattern after adsorption in an arsenic anion ion solution with a concentration below 100 ppm, proving that in a lower concentration arsenic anion ion solution, the material adsorbs arsenic anion ions mainly through ion exchange adsorption.

[0051] (3) The adsorption isotherm described in (1) was fitted with the Langmuir and Freundlich adsorption models, and the linear fitting equation was obtained, as shown in Figure 5 and Figure 6 It can be seen that the linear correlation coefficient R of the Langmuir and Freundlich adsorption models of the adsorption isotherm is 2They are 0.997 and 0.947 respectively, indicating that the Langmuir isotherm adsorption model can fit the measured adsorption isotherm well, indicating that the adsorbate is adsorbed on the adsorbent surface in a monolayer, the adsorption on the adsorbent surface is uniform, and there is no interaction between the adsorbates.

[0052] R L is a dimensionless separation factor defined from the Langmuir equation and is used to predict whether the adsorption process is favorable. L When R >1, it is unfavorable adsorption; L =1 for linear adsorption; R L =0 is irreversible adsorption; 0 <R L <1 is favorable for adsorption, and R L The closer it is to 1, the more conducive it is to the removal of pollutants.

[0053] Example 5

[0054] Study on the Adsorption Kinetics of As(V) by MAF-stu-2

[0055] (1) Weigh 10 mg of activated MAF-stu-2 powder material, add it to a 200 ppm arsenic anion ion aqueous solution, and place it in a constant temperature oscillator at 25 °C and 120 rpm. After sampling at different times, use ICP to test the residual arsenic anion ion content in the aqueous solution. The results are as follows: Figure 7 shown.

[0056] (2) After sampling as described in (1), samples of the adsorbent were taken at different times and the structural changes of the samples were detected by PXRD. The results are as follows: Figure 8 shown.

[0057] (3) When the time-varying curve of arsenic ion content in water described in (1) is obtained, the data are fitted with pseudo-first-order kinetic model and pseudo-second-order kinetic model. The results are as follows: Fig. 9 and Fig.10 As shown. It can be seen that the linear correlation coefficient R obtained by pseudo-first-order kinetic fitting and pseudo-second-order kinetic fitting 2 are 0.9529 and 0.9986 respectively, indicating that the pseudo-second-order adsorption kinetic model can fit the adsorption kinetic experimental results well, and the reaction rate is linearly related to the concentrations of the two reactants, indicating that the adsorption process is controlled by chemical action or chemical reaction, including chemical adsorption and ion exchange.

[0058] Example 6

[0059] Study on the performance of deep arsenic removal by MAF-stu-2

[0060] (1) Weigh 10 mg of the sample powder material and add it to a 10 ppm arsenic anion ion solution. Shake it at 25°C for 24 hours. Take samples at different time points, filter them, and use ICP to detect the arsenic ion concentration in the solution. The results are as follows: Fig.11 As shown. It can be seen that after 24 hours, the material can achieve a removal rate of 99.9% for arsenic ions in a 10 ppm solution. This result shows that the adsorbent material can achieve the removal of counter anions NO3 in the adsorbent at a lower concentration (<10 ppm) through the ion exchange mechanism. - With adsorbate AsO4 3- Quick exchange.

[0061] (2) The adsorption isotherm described in (1) was fitted with a pseudo-first-order kinetic model and a pseudo-second-order kinetic model. The results are shown in Fig.12 and Fig.13 As shown. It can be seen that the linear correlation coefficient R obtained by pseudo-first-order kinetic fitting and pseudo-second-order kinetic fitting 2 are 0.6839 and 0.9998 respectively, indicating that the adsorption process described in (1) is more consistent with the pseudo-second-order adsorption kinetic model, indicating that at lower concentrations, the adsorption of arsenic anions by this adsorbent is mainly based on ion exchange chemical adsorption.

[0062] (3) In order to study the anti-interference ability of the material to other ions in a complex system, 10 mg of MAF-stu-2 powder material was added with different concentrations (10 ppm and 100 ppm) of SO4 2- 、CO3 2- and Cl - The arsenic anion ion solution of ions was prepared and the anti-interference ability of the material to remove arsenic anion ions was tested. The results are as follows Fig.14 As shown, it is demonstrated that the adsorbent material can still exhibit excellent arsenic removal performance under the interference of common anions in sewage.

[0063] (4) In order to explore the cyclic adsorption performance of the material in low concentration As(V) solution, the MAF-stu-2 powder material was placed in a 10 ppm arsenic ion solution for saturated adsorption. It was then immersed in a 0.1 mol / L NaNO3 solution for one day, filtered, and re-immersed in a 20 ppm arsenic ion solution to measure the adsorption performance of the material. The above experimental steps were repeated twice. The results are as follows: Fig.15 As shown, this indicates that the adsorbent material exhibits good recyclability and regeneration capabilities in practical arsenic removal applications.

Claims

1. The application of ternary cationic framework MOF material MAF-stu-2 in deep arsenic removal in sewage is characterized by: The general structural formula of the ternary cationic framework MOF material MAF-stu-2 is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, where C 18 H 18 N6 is 1,3,5-tri(2-methyl-1H-imidazolyl)phenyl, NO3 - As counter anions, they are distributed on the pore surface and can exchange ions with arsenic anions in water; the crystal structure of MAF-stu-2 belongs to P -3 space group, a = b =22.2141(2) Å, c =11.3776(1)Å, α = β =90°, γ =120°.

2. The use according to claim 1, characterized in that: The preparation method of the ternary cationic framework MOF material MAF-stu-2 is as follows: zinc nitrate hexahydrate and an organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene are dissolved in methanol respectively, and then the methanol solution of zinc nitrate hexahydrate is added dropwise to the methanol solution of the organic ligand and rapidly stirred at room temperature, and after the addition is completed, the mixture is allowed to stand, filtered, washed, and dried; The mass ratio of zinc nitrate hexahydrate and organic ligand 1,3,5-tri(2-methyl-1H-imidazolyl)benzene added is 1:(1-1.2)。 3. A method for deep arsenic removal in sewage using ternary cationic framework MOF material MAF-stu-2, characterized in that: The method comprises soaking a ternary cationic framework MOF material MAF-stu-2 in sewage containing arsenic and leaving it to stand for 1-10 days; the structural formula of the ternary cationic framework MOF material MAF-stu-2 is [Zn3(C 18 H 18 N6)3(NO3)](NO3)5, where C 18 H 18 N6 is 1,3,5-tri(2-methyl-1H-imidazolyl)phenyl, NO3 - As counter anions, they are distributed on the pore surface and can exchange ions with arsenic anions in water; the crystal structure of MAF-stu-2 belongs to P -3 space group, a = b =22.2141(2) Å, c =11.3776(1)Å, α = β =90°, γ =120°.

4. The method according to claim 3, characterized in that: When the arsenic concentration in the sewage is greater than 200 ppm, the addition amount of the ternary cation framework MOF material MAF-stu-2 is 1-2 mg / mL, and the standing time is 1-10 days.

5. The method according to claim 3, characterized in that: When the arsenic concentration in the sewage is less than 10 ppm, the addition amount of the ternary cation framework MOF material MAF-stu-2 is 0.3-0.6 mg / mL, and the standing time is 1-2 days.

6. The method according to claim 3, characterized in that: When the arsenic concentration in the sewage is 10-200 ppm, the addition amount of the ternary cation framework MOF material MAF-stu-2 is 0.6-1 mg / mL, and the standing time is 1-5 days.

7. The method according to claim 4, characterized in that: The general structural formula of the compound obtained after standing is [Zn3(C 18 H 18 N6)2(AsO4)2], belongs to P 21 / n space group, a =16.31092(9), b =19.98092(11), c =24.46205(18)Å, α = γ =90°, β =107.3951(7)°.

Citation Information

Patent Citations

  • Arsenic removal adsorber and preparation method thereof

    CN108404872A

  • Ternary imidazole ligand zinc complex and preparation method thereof

    CN110330516A